(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the supervision of guidance and counseling at SMP Negeri 44 Palembang. It employs a qualitative descriptive approach with 15 informants selected through purposive sampling, consisting of the principal, head of the guidance and counseling unit, educators, students, and education staff. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, verification, and conclusion drawing. Data validity is ensured through source and technique triangulation, which guarantees reliable and valid results. The analysis results show that the supervision of guidance and counseling at SMP Negeri 44 Palembang is carried out through the stages of planning, implementation, evaluation, and follow-up. Planning is systematically structured by setting goals, targets, and success indicators aligned with student needs. Implementation is conducted in an organized manner by the principal and vice principal for student affairs, covering service observations, administrative evaluations, and program monitoring. Guidance counselors receive coaching based on supervisory results. Evaluations are conducted regularly at the end of each semester and academic year, involving the review of service documents and the administration of questionnaires and interviews with students and teachers